Chordoid Glioma of the Third Ventricle: A Case Report and a Treatment Strategy to This Rare Tumor - Chen, Xiao; Zhang, Benyan; Pan, Sijian; Sun, Qingfang; Bian, Liuguan (Frontiers in Oncology, 2020)
Chordoid glioma (CG) of the third ventricle is a rare type of brain tumor. Here, we present a case, review of the literature and proposed a treatment strategy for this rare tumor. Here, A 33-year-old woman presented with the menstrual disorder and progressive obesity. Magnetic resonance imaging showed a large irregularly circular tumor in the third ventricle. The tumor was subtotally resected by microsurgery via the right modified port approach. Immunohistochemical staining was positive for glial fibrillary acidic protein (GFAP), Vimentin and transcription termination factor-1 (TTF-1), and the Ki-67 proliferation index was low (5%), which indicating CG. Residual tumor decreased after treated by Gamma Knife radiosurgery (GKRS) with a dose of 15 Gy. During 30 months of follow-up, the tumor did not recur, and the patient suffered no complications. The diagnosis of CG requires a combination of clinical presentation, neuroimaging, and pathology. The ideal therapy is gross total resection (GTR) of the tumor. However, GTR is usually difficult and carries a high risk of postoperative complications because of the tumor location. This case indicates that planed subtotal resection followed by GKRS with a proper marginal dose could be a good treatment strategy for CG.